Playing with Moon Sand: a narrative inquiry into a teacher's experiences teaching alongside a student with a chronic illness. Issue 1 (2nd January 2016) - Davis, Beth; Murphy, M. Shaun
Abstract : This paper inquires into the experiences of an early childhood educator named Claire who taught a young girl with a chronic illness at East Willows Elementary School, a western Canadian elementary school. Using narrative inquiry as the methodology, Claire's experiences in her curriculum making alongside Madeline a young girl with Turner syndrome were explored and analyzed. In navigating through this curriculum around chronic illness, Claire negotiated liminal spaces between health and unhealth, sickness and wellness, capability and desire using stories of playful curriculum making. Through these liminal spaces, Claire created forward-looking stories of a new curriculum; a curriculum defined by playfulness, counterstories of play, the lived and planned curriculum, and the sharing of authority. This playful curriculum, this curriculum of play, became the negotiated story to live by for Claire and Madeline at East Willows Elementary School.